2022
DOI: 10.1155/2022/7900382
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Montmorillonite Functionalized Artificial Bone Scaffolds: Intercalation and Interlocking, Nanoenhancement, and Controlled Drug Release

Abstract: Montmorillonite (MMT) has attracted widespread attention in the field of bone tissue engineering in recent years because of its interlayer domain structure. The progress of MMT application was reviewed in this article. Concretely, the application of MMT was mainly explained from the structural characteristics, mechanical strengthening mechanism, organic functionalization, and drug loading and release. Firstly, the polar polymer molecular chains are easily induced into the interlayer domain of MMT to form an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 174 publications
(146 reference statements)
0
3
0
Order By: Relevance
“…The impregnation impacts the transformation of functional group changes from the bentonite, as shown by FTIR spectra in Figure 2. The multi-layer structure of bentonite established numerous octahedra hydroxyl groups indicated by stretching vibration peak at 3396 cm −1 (Li et al, 2022) . The broadening spectrum at 3380 cm −1 of vibration H-O-Si on NH-B was possibly due to the breaking of hydroxyl groups and water molecules in the surface coagulant (Langeroudi and Binaeian, 2018).…”
Section: Characterization Of Materialsmentioning
confidence: 99%
“…The impregnation impacts the transformation of functional group changes from the bentonite, as shown by FTIR spectra in Figure 2. The multi-layer structure of bentonite established numerous octahedra hydroxyl groups indicated by stretching vibration peak at 3396 cm −1 (Li et al, 2022) . The broadening spectrum at 3380 cm −1 of vibration H-O-Si on NH-B was possibly due to the breaking of hydroxyl groups and water molecules in the surface coagulant (Langeroudi and Binaeian, 2018).…”
Section: Characterization Of Materialsmentioning
confidence: 99%
“…In recent years, the addition of montmorillonite (MMT) to polymers [1] to improve their mechanical properties [2] has attracted widespread attention [3]. However, the inherent incompatibility between inorganic MMT [4] and organic polymers weakens the interfacial bonding between them [5], resulting in reduced mechanical properties of composite scaffolds filled with high content of MMT [6]. Therefore, it is of great significance to improve the compatibility between MMT and polymer [7].…”
Section: Introductionmentioning
confidence: 99%
“…1 In contrast, articial bone is attracting attention because it has a wide range of material sources and can obtain biological, mechanical, and degradation properties comparable to natural bone by modulating components. 2,3 Polycaprolactone (PCL) has been of great interest in bone tissue engineering due to its good biocompatibility, degradability, and processability. [4][5][6] However, some studies have shown that pure PCL scaffolds present challenges in terms of mechanical properties and biomineralization as bone implants.…”
Section: Introductionmentioning
confidence: 99%